Le territoire, un levier complémentaire pour l’atteinte du facteur 4 - Jacques Theys; Éric Vidalenc (Développement Durable et Territoires)
Energy and climate-related issues are getting more and more tackled in economic and techno-economic strategic foresight exercises in order to meet the 75% reduction of greenhouse gas emissions challenge by 2050 in France. However, when performed within the traditional conceptual and methodological frameworks, these exercises show how difficult it is to reach climate change objectives without shifting paradigm. Considering territorial aspects can provide complementary tools to traditional techno-economic strategic foresight exercises. This approach can also help to deal with these issues across-the-board, as well as to tackle governance-related issues at the local level. The Commissariat Général au Développement Durable (the French Sustainable Development General Commission) and the ADEME (the French Environment and Energy Management Agency) have jointly launched a research program called “Reconsidering cities in a post-carbon society” in order to emphasize the role of territorial aspects in the energy transition.